2013 6th International Congress on Image and Signal Processing (CISP) 2013
DOI: 10.1109/cisp.2013.6743975
|View full text |Cite
|
Sign up to set email alerts
|

Motion vector-based video steganalysis using spatial-temporal correlation

Abstract: In current media-centric society, video has become the suitable cover for steganography. However, video steganalysis remains largely unexplored compared to the mature image steganalysis. One open problem is how to design efficient rich features for video steganalysis by exploiting the correlations in video. In this paper, we propose a novel video steganalytic scheme based on the spatial-temporal correlation of motion vectors. The proposed scheme employs 324-dimension features from Markov matrix of motion vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Earlier methods use first order spatial filters but then the following methods integrated second order spatial filters as well. Then, Ye et al [28] showed that using temporal filters contributes to the accuracy which agrees what is shown in Fig. 2.…”
Section: Previous Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…Earlier methods use first order spatial filters but then the following methods integrated second order spatial filters as well. Then, Ye et al [28] showed that using temporal filters contributes to the accuracy which agrees what is shown in Fig. 2.…”
Section: Previous Methodssupporting
confidence: 73%
“…Therefore, in order to design a robust steganalytic system temporal dependency should also be taken into account. There are some methods which considers temporal dependency [9], [15], [19], [20], [28] and some other which does not [8], [16]- [18]. However, none of the previous methods considers temporally neighbouring frames further than one next or previous frames.…”
Section: Previous Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Zhang and XiJian, 6 the method of temporal and spatial correlation based on pixels is applied to steganographic method detection based on MV. Ye et al 7 used four-phase scanning to construct the symbiosis matrix to capture the abnormal changes in the space-time correlation of MVs caused by steganography. Tasdemir et al 8 transferred the SRM (Spatio Rich Model) applied in the field of image steganalysis into the video field, and detected the temporal and spatial characteristic changes of MVs in three dimensions, which has a good effect.…”
Section: Introductionmentioning
confidence: 99%